(untitled) (Bangladesh Journal of Neuroscience, 2017)
Background: Epilepsy is a common neurological disorder. Sodium valproate is one of the commonest broad spectrum antiepileptic drugs and it is used worldwide. Weight gain is the common side effect which is known to be associated with insulin resistance. The aim of this study was to see the association of sodium valproate therapy with insulin resistance among epileptic patients. Methods: It was a cross-sectional analytical study. Total 102 patients (51 epileptic patients with valproate monotherapy for at least one year and another 51 age and sex matched newly diagnosed epileptic patients without any anti-epileptic drugs) were selected in this study. The study was carried out from March 2016 to April 2017 for one year in the epilepsy clinic and outpatient Department of Neurology at Bangabandhu Sheikh Mujib Medical University, Dhaka. Participants underwent anthropometric evaluations and biochemical tests including fasting blood sugar and fasting insulin level. Insulin resistance (IR) index was calculated. Result: In this study mean duration of valproate treatment was 3.12±1.26 years and mean sodium valproate dose was 1133±440.5 mg/day (17.7±6.65 mg/kg/day). This study revealed serum fasting insulin level in valproate group and non-valproate group was 11.05±4.86 (ìU/ml) and 7.39±2.01 (ìU/ml) respectively. Fasting blood glucose was 4.71±0.79 (mmol/L) in valproate group and 4.41±0.62 (mmol/L) in non- valproate group. Calculated IR index in valproate group and non-valproate group was 2.17±0.55 and 1.46±0.39 respectively. IR index, fasting insulin and blood glucose all were significantly higher in valproate group than non- valproate group. This study also revealed mild positive correlation of IR index with dose and duration of valproate treatment. Conclusion: Sodium valproate treated patient had significantly higher IR index than control group. Bangladesh Journal of Neuroscience 2017; Vol. 33 (2): 63-69